Redefining Regional Development: The Case for an ASEAN Development Bank - Brice Tseen Fu Lee; Juan Pablo Sims (Journal of Political Issues)
Amidst ASEAN's vibrant economic expansion lies an urgent need for a specialized financial institution—an ASEAN Development Bank (ASDB)—to harness and guide this growth. The region's dynamic diversity in development stages presents a unique opportunity for the ASDB to act as the catalyst for economic resilience and regional integration. This urgency is underscored by the potential for the ASDB to provide targeted financial strategies, directly addressing the specific challenges faced by member states. A robust and equitable governance structure will be crucial for the ASDB to facilitate strategic decision-making and sustainable development. The establishment of the ASDB is not just timely but imperative to ensure that ASEAN's economic growth is balanced, inclusive, and sustainable, positioning the region as an integrated, resilient economic powerhouse on the global stage.